1985
DOI: 10.1111/j.1432-1033.1985.tb08703.x
|View full text |Cite
|
Sign up to set email alerts
|

A cytosol protease from the estrogen-resistant C3H mammary carcinoma increases the affinity of the estrogen receptor for DNA in vitro

Abstract: We have previously shown, in the estrogen-unresponsive C3H mouse mammary tumor that the affinity of the estrogen receptor (ER) for calf thymus DNA in vitro is four-times higher than that of uterine ER [Baskevitch, P. P., Vignon, F., Bousquet, C. and Rochefort, H. (1983) Cancer Res. 43,22901. By mixing cytosols from this tumor and uterus, we describe a tumor factor capable of increasing ER affinity for DNA, as assayed by DNA-cellulose chromatography and saturation studies. The activity of this factor was inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The tryptic peptides P1 and P2 have been aligned by sequence comparison with domains E/F. endopeptidases in C3H-mouse mammary tumour [26]. We took advantage of the limited receptor digestion by heparin-Sepharose-bound endogenous proteinase(s) from porcine uteri [4] and arrived at relatively stable, well-defined, fragments.…”
Section: Discussionmentioning
confidence: 99%
“…The tryptic peptides P1 and P2 have been aligned by sequence comparison with domains E/F. endopeptidases in C3H-mouse mammary tumour [26]. We took advantage of the limited receptor digestion by heparin-Sepharose-bound endogenous proteinase(s) from porcine uteri [4] and arrived at relatively stable, well-defined, fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolysis has been proposed as a mechanism for the activation of receptors t o forms with increased binding affinity for DNA (Hubbard et al 1984;Baskevitch and Rochefort 1985;Puca et al 1986). Horigome et al (1988) observed that the 54 000 but not the 37 000 fragment of the estrogen receptor of mouse uterus retained the ability to bind to DNA.…”
Section: Introductionmentioning
confidence: 99%
“…These responses are considered to be genomic responses to oestrogen, since they are blocked by inhibitors of RNA and protein synthesis (Ui & Mueller, 1963;Tchernitchin & Galand, 1982;Finlay, Katz, Kirsch et al 1983). This has led to the concept that genomic responses to steroid hormone stimulation are the result of the interaction of hormone-receptor complexes with regulatory DNA sequences (Payvar, Wränge, Carlstedt-Duke et al 1981;Mulvihill, LePennec & Chambón, 1982;Dean, Gope, Knoll et al 1984;Rousseau, 1984;Baskevitch & Rochefort, 1985;Jost, Geiser & Seldran, 1985;Moore, Marks, Buckley et al 1985;Shull & Gorski, 1985). This has led to the concept that genomic responses to steroid hormone stimulation are the result of the interaction of hormone-receptor complexes with regulatory DNA sequences (Payvar, Wränge, Carlstedt-Duke et al 1981;Mulvihill, LePennec & Chambón, 1982;Dean, Gope, Knoll et al 1984;Rousseau, 1984;Baskevitch & Rochefort, 1985;Jost, Geiser & Seldran, 1985;Moore, Marks, Buckley et al 1985;Shull & Gorski, 1985).…”
Section: Introductionmentioning
confidence: 99%